2014
DOI: 10.1371/journal.pone.0105257
|View full text |Cite
|
Sign up to set email alerts
|

Steller Sex: Infidelity and Sexual Selection in a Social Corvid (Cyanocitta stelleri)

Abstract: Genetic analysis of avian mating systems has revealed that more than 70% of monogamous species show incidence of offspring parentage that does not match the social partner. Extra-pair parentage (EPP) has been linked to a variety of factors, including size and symmetry of ornamental traits, coloration, resource availability, and local conspecific density. We examined how ornamental plumage traits of individual Steller's jays (Cyanocitta stelleri) and territory characteristics influence genetic fidelity of socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…For example, Steller’s jays’ plumage UV reflection signals mate quality. Note, however, that extra-pair copulations play a relatively important role for Steller’s jays, compared to other corvid species (Overeem et al 2014 ). It is thus unclear whether the importance of UV perception in Steller’s jays’ sexual behaviour is indicative of visual features that might be relevant for monogamous and largely unassisted breeding carrion crows.…”
Section: Discussionmentioning
confidence: 96%
“…For example, Steller’s jays’ plumage UV reflection signals mate quality. Note, however, that extra-pair copulations play a relatively important role for Steller’s jays, compared to other corvid species (Overeem et al 2014 ). It is thus unclear whether the importance of UV perception in Steller’s jays’ sexual behaviour is indicative of visual features that might be relevant for monogamous and largely unassisted breeding carrion crows.…”
Section: Discussionmentioning
confidence: 96%
“…In Steller's Jays, it is possible that brighter and more conspicuous facial features used for visual signaling in open habitats (Rocky Mountain morphotype) may be counterbalanced by selection for darker features (e.g., blue frontal streaks, no superciliary line) that are more cryptic in lower light, closed coastal forest habitats (Coastal morphotype). Plumage traits of individual Coastal Steller's Jays have been found to influence the rate of extra‐pair parentage and the proximity of territories to forest edge (Overeem et al, 2014). While studies have shown that selection in different habitats can be an important driver of phenotypic divergence, the outcome may be clade, environment, or sex‐specific (Cicero et al, 2020; Cornuault et al, 2015; Mason & Bowie, 2020; Medina et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Steller's Jays are relatively tolerant of human proximity; they lend themselves well to the examination of subtle behaviors, thus making jays a particularly well-suited species for behavioral studies. Prior research on this population has described a variety of individual variations in behavioral patterns, including optimal foraging [24], caching effort [25], novel problem solving [27], behavioral syndromes [30], assortative mating [32], and mate fidelity [36]. This research was conducted under the Cal Poly Humboldt Institutional Animal Care and Use Protocol No.…”
Section: Study Speciesmentioning
confidence: 99%